Implementation of Minister of Manpower Regulation Number 28 of 2014 Regarding PP PKB in the Manpower and Transmigration Service of East Java Province - Nabila Nur Aysyah; Magda Faradiba (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The East Java Provincial Manpower and Transmigration Office (Disnakertrans) in implementing Minister of Manpower Regulation No. 28 of 2014 strives to ensure that companies are required to create Company Regulations (PP), draft and ratify PP, and register Collective Labor Agreements (PKB). From January to September 2025, 107 companies had submitted their PP for ratification, while the registration of PKB continued according to procedure. This study aims to describe the efforts of the East Java Provincial Manpower and Transmigration Office in implementing Permenaker No. 28 of 2014 and to identify obstacles that arise in the field. This study applies a qualitative descriptive method, utilizing data collection techniques such as observation, interviews, and documentation. In its analysis, this study is guided by the policy implementation model proposed by George C. Edward III, which includes communication, resources, disposition, and bureaucratic structure. The results of the study show that communication is carried out through socialization, guidance, consultation, and the use of digital media. Employee resources and supporting facilities are considered sufficient to carry out the PP approval and PKB registration processes. Employee disposition shows a strong commitment to providing services and assistance to companies. The bureaucratic structure was clearly organized with workflows and SOPs that supported the smooth running of the process, although some companies still submitted incomplete documents, which required corrections and prolonged the verification process.